Self-Reliance Theory And Africa’s Drive Towards Development: Rethinking Globalisation In Nigeria’s Implementation Of The Sustainable Development Goals - Patrick Samuel Ekpe; Ifeanyi Martins Nwokeocha, PhD; George Nathan Brown; Vivian Ifeoma Okpalike; Mba, Precious Idongesit (International Journal of Education, Vocational and Social Science, 2025)
This study examines the intersection of self-reliance theory and Nigeria's implementation of the Sustainable Development Goals (SDGs) within the context of globalization. The research investigates how Nigeria can adopt a self-reliant approach to development, prioritizing domestic resources and capacities, to achieve the SDGs. The study employed a qualitative research approach, utilizing a case study design and thematic analysis to explore the role of self-reliance theory in Nigeria's SDGs implementation. The findings of the study indicate that self-reliance theory offers a promising framework for rethinking Nigeria's approach to development. The study highlights the need for Nigeria to adopt a self-reliant approach to development, promote African-led development initiatives, and develop a coherent national development strategy. The study recommends that Nigeria prioritize investment in human capital, promote entrepreneurship and innovation, strengthen institutional capacities, and promote regional integration and cooperation.